Bell Atlantic v. Twombly: How Motions to Dismiss Become (Disguised) Summary Judgments - Richard A. Epstein (Washington University Journal of Law & Policy, 2007)
The present Federal Rules of Civil Procedure allow a plaintiff’s case to be attacked either for its legal or factual sufficiency. The rules governing the former are in general adequate because judgments on the validity of claims do not require any discovery. Decisions before trial on factual matters are much more complex, especially in antitrust cases where discovery before a summary judgment motion can be highly expensive on open-ended claims of collusion over prices or territories. To counteract that risk, all courts today allow some judgments to be entered at the close of pleading and before discovery. The recent Supreme Court decision in Bell Atlantic Corp. v. Twombly, reversing the Second Circuit decision in Twombly v. Bell Atlantic Corp., resolved the ongoing dispute by requiring that a complaint contain “enough facts to state a claim to relief that is plausible on its face.” While the result of the decision is to be welcome, its analysis is flawed. In reality, Twombly III was a disguised motion for summary judgment that is best defended as properly balancing the relative error costs of stopping too soon or going too far. A close look at the record suggests that discovery would supply no new information of value, no matter how the case was pleaded. Therefore, the proper principle is that courts should be more willing to enter final judgments at the close of the pleadings, especially against plaintiffs whose claims are based solely on easily accessible public information which already have been rebutted by the same kinds of public evidence.
Keywords: Citizen suits (Civil procedure); Summary judgments; Motions to dismiss; Discovery (Law); Pleadings; United States; Bell Atlantic v. Twombly